Injury Patterns and Associated Demographics of Intimate Partner Violence in Older Adults Presenting to U.S. Emergency Departments. Issue 17 (September 2022) - Khurana, Bharti; Loder, Randall T.
Intimate partner violence (IPV) is a global public health issue and occurs in intimate relationships regardless of age or sexual orientation. Several studies, most of them relying on small-scale samples, have explored the prevalence and risk factors of IPV in older adults. Still, none have focused on the demographics and injury patterns in older adult victims. Using the National Electronic Injury Surveillance System (NEISS) All Injury Program (AIP) data, we performed a retrospective analysis from 2005 through 2015 of the demographics and injuries of older adult IPV patients (>60 years old) presenting to emergency departments (EDs) compared to younger adult IPV patients (<60 years old). IPV accounted for 2, 059, 441 ED visits (.61%) with 37, 534 (1.8%) visits in the older adults. Older adults were more frequently male (36.1% vs 16.8%), White (65.3% vs 52.8%), sustained fewer neck/head injuries (47.6% vs 59.4%), fewer contusions/abrasions (34.6% vs 47.2%), had more trunk fractures (38.4% vs 11.9%), trunk strains/sprains (39.5% vs 15.4%) and more hospital admissions (15.7 vs 4.2%), compared to younger IPV patients. Within the older adult cohort, females were more commonly White (71.2% vs 56.0%) while males were more commonly Black (36.3% vs 19.0%). Injuries in older adult males were more commonly lacerations (40.6% vs 14.2%%) and less commonly contusions/abrasions (33.8% vs 43.5%) compared to elderly females. Older adult females had more internal organ injuries than older adult males (18.9% vs 12.9%) and nearly all involved the head. Knowledge of these injury patterns in older adults can equip the health care providers when to be more suspicious of unexplained or suspicious injuries as the victim's symptoms at the presentation might not be directly related to violence.